Early Childhood Special Science Education: Setting the frame of a newly born and well-promising trend - GEORGE KALIAMPOS (Metaichmio Publications, 2021)
The last three decades two distinct trends have emerged within Early Childhood Education, namely Early Childhood Science Education and Early Childhood Special Education. The current paper tries to move along these areas and illuminate the common ground that lie between them. In particular, drawing from the formulated empiricist, Piagetian and socio-cognitive trends within Early Childhood Science Education, it tries to explore to what extend they could expand in special needs context. In addition, it proposes diverse, specific strategies that emerge from the above-mentioned trends and could be implemented in teaching science within special needs settings. By so doing, the present paper aspires to set the frame of a newly born and well-promising trend, that of Early Childhood Special Science Education.